2008
DOI: 10.1182/blood-2007-04-084756
|View full text |Cite
|
Sign up to set email alerts
|

The antileukemia activity of a human anti-CD40 antagonist antibody, HCD122, on human chronic lymphocytic leukemia cells

Abstract: B-cell chronic lymphocytic leukemia (B-CLL IntroductionChronic lymphocytic leukemia (CLL) is the most common adult leukemia in the United States and is characterized by progressive accumulation of malignant B cells in the blood, bone marrow, and lymphoid organs. CLL has been considered a prime example of a malignancy involving defects in the regulation of cell death; the slow accumulation of B-cell CLL (B-CLL) cells is presumably the result of a low proliferative index coupled with an intrinsic defect in apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 76 publications
0
66
0
Order By: Relevance
“…27 Not all CLL clones respond to CD40 stimulation in vitro, indicating a clonal functional heterogeneity. 1,17,18 This is relevant considering that CD40 has attracted great interest as a potential therapeutic target in CLL, 28,29 and in ongoing clinical trials either activation of CD40 by genetically modified leukemic cells expressing CD40L gene 30 or CD40 inhibition with anti-CD40 antagonist antibody 31 are used in different therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…27 Not all CLL clones respond to CD40 stimulation in vitro, indicating a clonal functional heterogeneity. 1,17,18 This is relevant considering that CD40 has attracted great interest as a potential therapeutic target in CLL, 28,29 and in ongoing clinical trials either activation of CD40 by genetically modified leukemic cells expressing CD40L gene 30 or CD40 inhibition with anti-CD40 antagonist antibody 31 are used in different therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In our studies of therapeutic mAb, their potency is unprecedented, clearing bulk tumors from mice with established disease and providing immunity to rechallenge (20,24). To date, four anti-CD40 mAb 893 (31), , HCD122 (26,33)], and Chi LOB7-4 (34) have been investigated in phase I/II trials. These reagents show diverse activities ranging from antagonist (HCD122) to strong agonist (CP-870,893) (26).…”
mentioning
confidence: 99%
“…33 Extensive in vitro studies identified many pathways and factors that enhance CLL cell survival and promote limited proliferation, including TLRs, cytokines, chemokines, CD40, B-cellactivating factor of tumor necrosis factor family (BAFF), integrins, and components of the extracellular matrix. 22,25,31,[34][35][36][37][38] Many of these extrinsic factors signal through SYK, PI3K␦, and BTK and activate similar intracellular pathways, most prominently the PI3K/ AKT/mTOR, NF-B, and MAPK pathways. It is therefore difficult to estimate to what degree any single factor or pathway may be necessary or sufficient for CLL pathogenesis.…”
Section: Bcr Signaling In Cllmentioning
confidence: 99%